Orientasi Seksual; Faktor, Pandangan Kesehatan dan Agama - Alhamdu, Alhamdu (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2015)
The purpose of this study is looking for factors that have contrubuting to sexsual orientation development empirically, and want to know how the health and religion views about sexsual orientation. Based on literature, the writer find three factors that have contrubuted to sexsual orientation development, namely developmental processes, social and culture,and heredity (genetic and hormonal). In other hand the study also find that th negative sexual orientations (including homosexsual and bisexsual) have higher tendency to become unhealty and have diseas such as sypilis, hephatitis B and HIV. Scholars find that the religious obedience can be delay implementation of negative sexual orientation.